Emma Goldman: A Documentary History of the American Years, Volume One : Made for America, 1890-1901 - Goldman, Emma (Book collections on Project MUSE., 2003)
Emma Goldman: A Documentary History of the American Years redefines the historical memory of Emma Goldman and illuminates a forgotten yet influential facet of the history of American and European radicalism. This definitive multivolume work, which differs significantly from Goldman's autobiography, presents original texts-a significant group of which are published in or translated into English for the first time-anchored by rigorous contextual annotations. The distillation of years of scholarly research, these volumes include personal correspondence, newspaper articles, government surve.